Feasibility Study of Quail Farming Business at Nurul Quran Islamic Boarding School in Bali, Indonesia - Rizki Prafitri; Dina Marliana; Khaerunnisa Firdaus Sadikin; Ahmad Nur Musyarrof Al Akrom; Muhammad Halim Natsir; Nanang Febrianto; Dyah Lestari Yulianti; Osfar Sjofjan (Faculty of Animal Science, Universitas Brawijaya, 2023)
Nurul Quran Islamic boarding school (so called pondok pesantren in Bahasa Indonesia) would develop a quail farming business to provide agriculture skills and develop entrepreneurship for the students and alumni. Quail farming is selected because it is relatively easy, lucrative, has productivity up to 90%, produces 130-300 eggs per week, and does not require an extensive farming area. This study aims to analyze the feasibility study of the quail farming business at Nurul Quran Islamic boarding school, Bali, Indonesia. The method used in this study was purposive sampling. The economic analysis includes cost, revenue, Return on Investment and SWOT analysis. The findings indicate that the quail farming business will be most efficient at a scale of 3,000 birds with a total cost of Rp 214,849,351 and total revenue of Rp 297,975,000 per period. The return per cost of the business is 1.39; the boarding school will achieve a return of investment up to 51.22%. The SWOT analysis shows that the quail farming business at the boarding school has an excellent opportunity. However, the boarding school should have some strategies to minimize the weaknesses and threats that could challenge the business. The boarding school needs to develop human resources before starting the business, maximize the potential of the boarding school, market access, technology, and networking with the Muslim community as the marketing strategy for the quail farming business.